Das trevas da floresta à luz da civilização cristã : práticas missionárias dos capuchinhos da Úmbria no Alto Solimões (1910-1960) - Argañaraz, Silvina Bustos (UFRJ, 2004)
[PT]Esta dissertação consiste em um estudo de caso sobre as práticas de um grupo de missionários da Ordem dos Frades Menores Capuchinhos, oriundos da Úmbria (Itália), na região do Alto Solimões (estado do Amazonas) desde sua instalação em 1910, até os anos prévios ao Concílio Vaticano II (1962-1965). O objetivo central é dimensionar o processo social de criação de unidades básicas de ocupação territorial – denominadas na linguagem eclesiástica da época territórios de missão – na tentativa de refletir sobre as modalidades eclesiásticas de gestão e conhecimento de territórios e populações. Tem especial importância na dissertação a descrição dos mecanismos específicos de exercício cotidiano do poder eclesiástico e das técnicas de representação desse exercício, como as exibidas nas exposições missionárias realizadas no Vaticano, em 1925 e 1950, e no Brasil, em 1942 e 1955. Focalizando o processo histórico de construção de um território de missão no Alto Solimões, faz-se uma descrição tanto das combinações de diferentes ‘escalas’ implicadas na configuração desse território, quanto da variação de contextos múltiplos, do mais local ao mais global, nos quais inscrevem-se as práticas dos capuchinhos úmbrios. A perspectiva das ‘escalas’ afigura-se como fundamental na leitura feita acerca das experiências de um indivíduo, de um grupo e de um espaço, para perceber uma modulação particular do processo de territorialização da Igreja católica, como organização social empírica.[EN]This dissertation reflects the results of a case study focused on the practices of a group of missionaries from the Order of Friars Minor Capuchin. The monks involved were from Umbria (Italy), and their work took place in the Alto Solimões region of the state of Amazonas, in Brazil, between their arrival in 1910 and the years preceding the Vatican II Council (1962-1965). The main goal of the study is to assess the social process linked to the creation of basic units for territorial occupation – which were referred to as mission territories in the church terminology of that period. The purpose is to reflect on the church’s methods for knowledge-acquisition and management of territories and local populations. Particularly relevant within this study is the description of specific mechanisms through which the church’s power was exercised on an everyday basis. Consequently, the description of techniques through which such exercise of power was represented (such as the exhibitions conducted at the Vatican in 1925 and 1950, and in Brazil in 1942 and 1955), is also highly relevant. Focusing on the historical process of building a mission territory in Alto Solimões amounts to describing two factors: First, the combination of different ‘scales’ involved in the configuration of said territory. Second, the changes in multiple contexts (from the most local to the most global) within which the practices of the Capuchins from Umbria take place. The ‘scales’ perspective is fundamental when examining the experiences of an individual, a group and a spatial context, as a way to perceive the specific succession of stages within the territorialization process carried out by the Catholic Church as an empirical social organization.